An Efficient Biometric Authentication Protocol for Wireless Sensor Networks - Ohood Althobaiti; Mznah Al-Rodhaan; Abdullah Al-Dhelaan (International Journal of Distributed Sensor Networks, 2013)
Wireless sensor networks (WSNs) are spreading rapidly due to their flexibility to communicate which demands a secure environment. The most important requirements of WSN security are confidentiality, authentication, and integrity. User authentication is necessary for legitimate access control in WSNs. Sensors have limited processing power, bandwidth, memory, and limited communication abilities. Significantly, the system must produce an authentication method to confirme if the user is legal or not. In this paper, we present a solution based on biometric and adapt it for a WSN environment. The proposed protocol involves simple operations and light computations. The main advantage of the proposed protocol is using the user's iris to regenerate the user's key on-the-fly every time the user wants be authenticated which dramatically enhances security aspects in WSNs. The key used in this protocol is stronger than passwords and shorter than biometric data, which balances between security and performance. Our protocol uses much light computations and simple operations in both homogenous and heterogeneous environments; therefore, it is suitable to the WSNs.